Novel general active reliability redundancy allocation problems and algorithm - Yeh, Wei-Chang; Zhu, Wenbo; Tan, Shi-Yi; Wang, Gai-Ge; Yeh, Yuan-Hui (Reliability engineering & system safety, 2022)
•novel general active reliability redundancy allocation problems (GRRAP).•novel small-sampling tri-objective orthogonal array (SS3OA) to tune parameters.•new simplified swarm optimization (SSO) based on SS3OA.•combination of SSO and the binary-addition-tree algorithm (BAT).•new algorithm called BAT-SSOA3 for GRRAP. The traditional (active) reliability redundancy allocation problem (RRAP) is used to maximize system reliability by determining the redundancy and reliability variables in each subsystem to satisfy the volume, cost, and weight constraints. The RRAP structure is very simple, that is, redundant components are parallel in each subsystem, and all subsystems are either connected in series or in a bridge network. Owing to its important and practical applications, a novel RRAP, called the general RRAP (GRRAP), is proposed to extend the series-parallel structure or bridge network to a more general network structure. To solve the proposed novel GRRAP, a new algorithm, called the BAT-SSOA3, used the simplified swarm optimization (SSO) to update solutions, the small-sampling tri-objective orthogonal array (SS3OA) to tune the parameters in the proposed algorithm, the binary-addition-tree algorithm (BAT) to calculate the fitness (i.e., reliability) of each solution, and the penalty function to force infeasible back to the feasible region. To validate the proposed algorithm, the BAT-SSOA3 is compared with the boundary SSO (BSO), which is the best-known SSO-based algorithm for the RRAP, via designed experiments and computational studies.